Nanocápsulas contendo ácido ferúlico: desenvolvimento, avaliação da segurança e citoproteção em células mononucleadas humanas - Rampelotto, Camila Reck (2020)
Ferulic acid is a phenolic compound that has antioxidant, anti-inflammatory and anticarcinogenic properties. However, it has limited oral bioavailability, challenging its therapeutic application. Thus, polymeric nanocapsules are carriers of substances of pharmaceutical interest and may be delineated to mitigate undesirable effects, improve stability and biological performance of the substances. In this way, the present investigation aimed to develop ferulic acid loaded-nanocapsule suspensions and evaluate their in vitro scavenging capacity, particle interaction and irritation potential with mucous membrane, cytocompatibility, cytoprotection and genoprotection in human mononucleated cells against oxidative stress. From the results, it was possible to obtain nanocapsules containing ferulic acid at a concentration of 0.5 mg/mL, with adequate physicochemical characteristics (112 ± 3 nm; IPd: 0.10 ± 0.01; PZ: -7,0 ± 0.4 mV; 100.9 ± 0.9 % ferulic acid relative content). The nanocarriers promoted controlled release of ferulic acid in hydrochloric medium pH 2.0; its potentiated ABTS radical inhibition, interact with mucin and reduce irritation potential, demonstrated by HET-CAM test. In the cytotoxicity tests, the nanocapsules proved to be cytocompatible, as well as promoted cytoprotection and genoprotection front hidrogen peroxide. Moreover, it was possible to obtain suitable dispersible dried products from freeze-drying of nanocapsule suspensions, improving the stability of ferulic acid relative to aqueous suspensions. Considering the results, the association of ferulic acid with ethylcellulose polymeric nanocapsules showed be an important and promising technological strategy to enable its prophylactic and/or therapeutic application.